10 Implementasi Kebijakan Program Bantuan Langsung Tunai (BLT) Di Desa Situwangi - Putri, Risa Amalia; Munawar, Muhammad Fikri; Yulianti, Rianamasri; A, T. Tutut Widiastuti (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
In the reality of problems in life, poverty is a social problem that is not foreign to developing countries, especially in Indonesia, present in various forms and conditions that are quite alarming. So the government makes policies and programs to reduce the problem of poverty in this country. The Direct Cash Assistance (BLT) program is a government program given to the community taken from the Village Fund budget in 2022, which is set at around 40% of the total amount of Village funds budgeted in 2022 to be used for Direct Cash Assistance (BLT). Evaluation is also needed to see if a program is effective and right on target so it is possible to do several methods in this research, Participatory Action Research (PAR) Through this approach the process aims for learning in overcoming problems and meeting community needs. We conducted interviews with several resource persons, and the first interview was conducted on July 27, 2023 with the resource person, according to the local community, the BLT funds provided by the government were still not on target, because the BLT funds were not evenly distributed. In the implementation of BLT funds, there are still people who do not receive BLT benefits, this happens because of social jealousy between people who receive assistance and people who do not receive assistance.